Intervensi Terapi Music Dan Aromaterapi Terhadap Kecemasan Pada Pasien Bedah Digestive Pre Operative Laparotomi : A Systematic Review - Nurul Imam; Taufan Citra Darmawan; Alfid Tri Affandi; Pradita Ayu Fernanda (KHD Production, 2024)
Laparotomy is a surgical procedure to open the abdominal cavity, with an incision in the abdominal wall to access the organs. Laparotomy can cause anxiety in the patient. Management that may be given to reduce anxiety is music therapy and aroma therapy. Both of these therapies stimulate the brain to change emotions. Anxiety before surgery has an impact on the results of surgery which can cause hypertension, increase heart rate, and can cause bleeding. This study aims to explain the effect of music therapy and aromatherapy interventions on anxiety in digestive surgery patients before laparotomy surgery. The research design used the Preferred Reporting Items for Systemic Review guidelines with an online literature search strategy using the Scopus, Science Direct, PubMed and ProQuest databases. The years of literature sources taken are 2014 to 2023. Research from 19 journals reviewed showed that there was an effect of a combination of music therapy and aromatherapy on anxiety in preoperative laparotomy digestive surgery patients. The articles reviewed were based on inclusion criteria. The results of the review of all articles showed that music therapy and aromatherapy were effective in overcoming anxiety in patients who were going to undergo laparotomy surgery. This intervention can reduce the impact or complications that may occur after laparotomy surgery. Music therapy and aromatherapy are effective interventions used as therapy to reduce anxiety levels before laparotomy surgery and can be used as independent nursing interventions that are easy and cheap to implement and have excellent benefits for patients.